An injectable silk fibroin nanofiber hydrogel hybrid system for tumor upconversion luminescence imaging and photothermal therapy. (15th January 2019) - He, Wei; Li, Po; Zhu, Yue; Liu, Mingming; Huang, Xiaonan; Qi, Hui
Abstract : In this paper, we developed a silk fibroin nanofiber (SF) hydrogel system complexed with upconversion nanoparticles and nano-graphene oxide (SF/UCNP@NGO) for upconversion luminescence imaging and photothermal therapy. Abstract : In this paper, we developed a silk fibroin nanofiber (SF) hydrogel system complexed with upconversion nanoparticles and nano-graphene oxide (SF/UCNP@NGO) for upconversion luminescence imaging and photothermal therapy. The NaLuF4 :Er 3+, Yb 3+ upconversion nanoparticles were complexed with the nano-graphene oxide composite by a ligand exchange strategy, and then doped into an aqueous SF solution to form a hybrid hydrogel system. In vitro studies demonstrated that the SF/UCNP@NGO hydrogels possessed excellent biocompatibility and were capable of efficiently ablating cancerous cells via the photothermal effect. In vivo antitumor studies further confirmed that the SF/UCNP@NGO hydrogels could present outstanding antitumor efficacy. This work presents a novel hydrogel system, which could not only act as tumor imaging probes, but could also serve as therapy agents.